Evaluation of Synthetic 2,4-Disubstituted-benzo[g]quinoxaline Derivatives as Potential Anticancer Agents - Islam Zaki; Sara A. Abu El-ata; Eman Fayad; Ola A. Abu Ali; Ali H. Abu Almaaty; Ahmed S. Saad (MDPI AG, 2021)
A new series of 2,4-disubstituted benzo[g]quinoxaline molecules have been synthesized, using naphthalene-2,3-diamine and 1,4-dibromonaphthalene-2,3-diamine as the key starting materials. The structures of the new compounds were confirmed by spectral data along with elemental microanalyses. The cytotoxic activity of all synthesized benzo[g]quinoxaline derivatives was assessed in vitro against the breast MCF-7 cancer cell line. The tested molecules revealed good cytotoxicity toward the breast MCF-7 cancer cell line, especially compound 3. The results of topoisomerase IIβ inhibition assay revealed that compound 3 exhibits potent inhibitory activity in submicromolar concentration. Additionally, compound 3 was found to cause pre-G1 apoptosis, and slightly increase the cell population at G1 and S phases of the cell cycle profile in MCF-7 cells. Finally, compound 3 induces apoptosis via Bax activation and downregulation of Bcl2, as revealed by ELISA assay.